Pediatric Residency Graduates Preparedness for Neonatal-Perinatal Medicine Fellowship: The Perspective of First-Year Fellows - Korbel, Lindsey; Backes, Carl H., Jr; Rivera, Brian K.; Mitchell, Courtney C.; Carbajal, Melissa M.; Reber, Kristina; Bonachea, Elizabeth M. (American Journal of Perinatology, 2020)
Objective This study aimed to report on Neonatal-Perinatal Medicine (NPM) fellows' views of self-preparedness upon starting postresidency training.Study Design We conducted a national survey of first-year NPM fellows in the United States. The validated survey had five major areas: professionalism, psychomotor ability, independence/graduated responsibility, clinical evaluation, and academia. Survey responses were analyzed using descriptive statistics, and the free-text answers were categorized.Results Of 228 potential first-year NPM fellows, 140 (61%) initially responded to the survey. Overall, the fellows perceived themselves positively in professionalism and independence/graduated responsibility domains. Marked variability was observed in perceived preparedness in psychomotor ability, with confidence in neonatal intubation and arterial line placement of 86 and 49%, respectively. Lack of confidence in performing neonatal intubation procedures correlates with lack of attempts. The majority (75%) of fellows reported being interested in academia, but less than half felt capable of writing an article.Conclusion First-year NPM fellows identified deficiencies in the domains of psychomotor ability and academia. Residency and fellowship programs should partner to address these deficiencies.
Keywords: medical education; neonatal-perinatal medicine; pediatric residency